WP1066 Sensitizes Oral Squamous Cell Carcinoma Cells to Cisplatin by Targeting STAT3/miR-21 axis - Zhou, Xuan (Sci Rep, 2014)
Accumulating evidence reveals that activation of STAT3 and miR-21 contributes to chemoresistance in multiple tumors. We examined the expression of STAT3 and miR-21 in 43 oral squamous cell carcinoma (OSCC) tumors and classified them into cisplatin sensitive or resistant group. Tca8113 and Tca8113/DDP cells were treated with cisplatin (DDP), WP1066 (STAT3 inhibitor) or in combination. MTT, colony formation, wound healing, 3-D culture, and transwell chamber assays were used to evaluate the malignant phenotype of OSCC cells. We evaluated the effect of WP1066 on the expression of STAT3 and miR-21. A Tca8113/DDP OSCC xenograft tumor model was established to evaluate the therapeutic effect of WP1066 in combination with DDP. The expression of STAT3/miR-21 was significantly increased in DDP-resistant OSCC samples and Tca8113/DDP cells compared to its parental cell. Treatment of DDP combined with WP1066 efficiently inhibited Tca8113 and Tca8113/DDP cell proliferation, migration and invasion. STAT3 mediated OSCC cell survival and DDP resistance through upregulating the expression of miR-21 and downregulating miR-21 downstream targets, including PTEN, TIMP3 and PDCD4. WP1066 plus DDP treatment could inhibit Tca8113 and Tca8113/DDP cell growth by inhibiting STAT3 phosphorylation and miR-21 expression. These results indicated that STAT3/miR-21 axis could be a candidate therapeutic target for OSCC chemoresistance.